PP64 Cocoa bean shell (Theobroma cacao L.): A waste from the Colombian agro-industry with bioactive compounds. - Higuera Diaz, Daniel Alberto; Salazar Rengifo, Albeiro; Torres Castañeda, Harlen Gerardo; Cedeño-Fierro, Valeria; Andrade Mahecha, Margarita Maria; Martinez Correa, Hugo Alexander (Revista Productos Naturales, 2025)
n this research, two samples of cocoa bean shell (Theobroma cacao L.) originating from Huila, Tolima, Caldas and Cauca were used to extract the bioactive compounds present in the cocoa bean shell by using five solvent mixtures, including three natural deep eutectic solvents (NaDES). The results showed that the extracts obtained with Choline Chloride – Glycerol was the highest yield of phenolic compounds. Based on these results, the antioxidant capacity was estimated using the free radical method of ABTS and the radical DPPH.